Diversity of larger fungi in coniferous communities of Shar Mountain National Park (Republic of North Macedonia) with new country records. - Jashari, H.; Tofilovska, S.; Karadelev, M.; Rusevska, K. (Ecologia Balkanica, 2023)
Shar Mountain is one of the largest mountain ranges in Republic of North Macedonia, distinguished by outstanding biodiversity, first and foremost owing to the presence of various climate and vegetation features. Published data on the mycota of Shar Mt. is scarce; they refer to specific areas, and there are no systematic data available on occurrence of the species in different forest associations. Therefore, we decided to embark on mycodiversity study of the coniferous communities in this mountain. The material was collected in 2021 and 2022, from six localities: Popova Shapka, Jelak, Shipkovica, Leshnica, the Adzhina Reka river - in natural coniferous woods, and in pine plantations from the vicinity of Rogachevo village. The study resulted in recording of 179 species, two lichenized fungi, and one fungus-like organism. The total number of macromycetes from coniferous communities of Shar Mt. is 214. The phylum Basidiomycota comprises 170 species (where of 6 are gasteroid fungi); 6 species are referred to Ascomycota. It is worth noting the finds of Agaricus altipes, Cortinarius flexipes, C. triformis, Lyophyllum konradianum and Pluteus primus, which are first data for Republic of North Macedonia.
Keywords: macrofungi, Picea and Abies forests, new data records, Shar NP.